Mitigating fraud risk in payment system via e-wallet implementation: determining user acceptance in Indonesia / Machmudin Eka Prasetya - Prasetya, Machmudin Eka (2022)
Credit and debit cards were the first digital payment innovations, followed by internet banking, mobile banking, e-payments, and mobile payments, which are now considered the most recent innovations in e-wallet payment. Despite its benefits, e-wallet payment usage in Indonesia remains low when compared to total internet users, particularly mobile internet users, because e-wallet is typically used on a mobile phone(smartphone). The purpose of this research is to describe how e-wallet payments can mitigate the risk of fraud in traditional cash payments and to empirically investigate the factors influencing the acceptance of e-wallet payment systems among Indonesian users. The study was divided into two sections: the first addressed how e-wallet payment could reduce fraud risk, and the second area of the study addressed factors determining the acceptance of e-wallet payment in Indonesia.